2015
DOI: 10.1371/journal.pone.0130328
|View full text |Cite
|
Sign up to set email alerts
|

Asian Citrus Psyllid Expression Profiles Suggest Candidatus Liberibacter Asiaticus-Mediated Alteration of Adult Nutrition and Metabolism, and of Nymphal Development and Immunity

Abstract: The Asian citrus psyllid (ACP) Diaphorina citri Kuwayama (Hemiptera: Psyllidae) is the insect vector of the fastidious bacterium Candidatus Liberibacter asiaticus (CLas), the causal agent of citrus greening disease, or Huanglongbing (HLB). The widespread invasiveness of the psyllid vector and HLB in citrus trees worldwide has underscored the need for non-traditional approaches to manage the disease. One tenable solution is through the deployment of RNA interference technology to silence protein-protein interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(110 citation statements)
references
References 127 publications
(131 reference statements)
6
94
0
2
Order By: Relevance
“…In addition, glycerol kinase, which is involved in triglyceride breakdown, and aldose-L-epimerase, which is involved in glycolysis, were upregulated in CLas-infected D. citri psyllids (36). In addition, the comparative transcriptomic analysis of CLas infection altered the expression of many genes involved in nutrient reservoir activity in D. citri (37). The gene expression results indicated that CLas alters its host environment to make the nutrients more available (37).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, glycerol kinase, which is involved in triglyceride breakdown, and aldose-L-epimerase, which is involved in glycolysis, were upregulated in CLas-infected D. citri psyllids (36). In addition, the comparative transcriptomic analysis of CLas infection altered the expression of many genes involved in nutrient reservoir activity in D. citri (37). The gene expression results indicated that CLas alters its host environment to make the nutrients more available (37).…”
Section: Resultsmentioning
confidence: 97%
“…In addition, the comparative transcriptomic analysis of CLas infection altered the expression of many genes involved in nutrient reservoir activity in D. citri (37). The gene expression results indicated that CLas alters its host environment to make the nutrients more available (37). Although our results showed that ATP synthesis was increased and its consumption was decreased in CLas-infected D. citri psyllids, the results indicated that the increased ATP synthesis may contribute more to the accumulation of ATP level than the decrease in consumption.…”
Section: Resultsmentioning
confidence: 99%
“…Also included were published sequences produced by recent deep sequencing surveys of D. citri (Hunter et al, 2014; Vyas et al, 2015). Immune related genes of interest were selected based on previous surveys of arthropod immune pathways and immunological defenses (Gerardo et al, 2010; GonzĂĄlez-Santoyo and CĂłrdoba-Aguilar, 2011; Buchon et al, 2014; Smith and Pal, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…In other Hemipterans described in this review, it also appears that, like in aphids, there is a reduction in the immune potential of these insects when compared to insects with complete metamorphosis (Kliot et al ., ; Vyas et al ., ) (Table ). Nevertheless, the titer of nutritional endosymbionts of aphids, psyllids, and whiteflies appear to be modulated by facultative endosymbionts and plant pathogens (Kliot et al ., ; Vyas et al ., ). In consequence, there may be interplay of host immune responses to other microbe associates that are not long‐term endosymbionts.…”
Section: Discussionmentioning
confidence: 99%
“…While the relationship between polyketide synthesis and Liberibacter infection is unclear, this suggests that Profftella endosymbionts respond to Liberibacter infection either directly or indirectly (Ramsey et al, 2015). In another study, genes associated with the insect immune response were downregulated in D. citri nymphs that were infected with Liberibacter, suggesting that bacteria are in fact able to induce a lowered immune response to enhance transmission and infection (Vyas et al, 2015). Additionally, nymphal stages are more susceptible to infection by Liberibacter than adult stages, lending to the idea that Liberibacter manipulates and exploits different D. citri life stages to maximize propagation (Vyas et al, 2015).…”
Section: Regulation Of Symbiont Titer Throughout Insect Developmentmentioning
confidence: 99%